The Economy in the Time of Covid-19 - World Bank (Washington, DC: World Bank, 2020)
After a period of rapid economic growth associated with high commodity prices, the region had entered a phase of lackluster performance. Recent developments, including a new oil price shock, and the outbreak of the Covid-19 epidemic will push the region into recession. Many countries are struggling to contain the spread of the Covid-19 epidemic while avoiding a dramatic decline in economic activity. The report analyzes how to think about this tradeoff. It estimates the potential health costs, assesses the effectiveness of diverse containment strategies, and discusses how large the economic cost could be. The current crisis is unprecedented because it combines a fall in global demand, tighter financial conditions and a major supply shock. The response needs to consider how to socialize the losses, how to prevent a collapse of the financial sector, how to protect jobs and livelihoods, and how to manage and divest the assets that will inevitably end up in the hands of the state.